Effects of dietary addition of ellagic acid on rumen metabolism, nutrient apparent digestibility, and growth performance in Kazakh sheep - Zhang, Wenjie; Ren, Feier; Zang, Changjiang; Yang, Fan; Li, Xuanyue; Huang, Xinxin; Chen, Kaixu; Li, Xiaobin (Frontiers in Veterinary Science, 2024)
Plant extracts have shown promise as natural feed additives to improve animal health and growth.Ellagic acid (EA), widely present in various plant tissues, offers diverse biological benefits. However, limited research has explored in its effects on ruminants. This study aimed to investigate the effects of dietary addition EA on rumen metabolism, apparent digestibility of nutrients, and growth performance in Kazakh sheep. Ten five-month-old Kazakh sheep with similar body weight (BW), fitted with rumen fistulas, were randomly assigned to two groups: CON group (basal diet) and EA group (basal diet + 30 mg/kg BW EA). The experiment lasted for 30 days, and individual growth performance was assessed under identical feeding and management conditions. During the experimental period, rumen fluid, fecal, and blood samples were collected for analysis. Results indicated a trend toward increased average daily gain in the EA group compared to CON group (p=0.094). Compared with CON group, the rumen contents of acetic acid and propionic acid were significantly increased in the EA group, and reached up to highest value at 2 h to 4 h after feeding (p<0.05). Moreover, the relative abundances of specific rumen microbiota (Ruminococcaceae, uncultured_rumen_bacterium, unclassified_Prevotella, Bacteroidales, Bacteroidota, Bacteroidia, unclassified_Rikenellaceae, and Prevotella_spBP1_145) at the family and genus levels were significantly higher in the EA group (p<0.05) compared to the CON group. The EA group exhibited significantly higher dry matter intake (p<0.05), and increased digestibility of neutral detergent fiber and ether extract when compared to CON group (p<0.05). Additionally, the plasma activities of total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase(GSH-Px) were significantly higher, while malondialdehyde (MDA) concentration was significantly lower in the EA group compared to the CON group (p<0.05). In conclusion, dietary supplementation with 30 mg/kg BW EA in five-month-old Kazakh sheep increased the dry matter intake, apparent digestibility of neutral detergent fiber and ether extract, as well as the contents of acetic acid and propionic acid in rumen fluid. Moreover, EA supplementation regulated the ruminal microbiota, enhanced antioxidant capacity and improved daily weight gain.